Franchise termination laws, craft brewery entry and growth - Jacob Burgdorf (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2021)
This paper estimates how beer franchise laws and their interaction with restrictions on vertical integration between manufacturing and wholesaling impacted US craft brewers' entry and production decisions. The effects are identified by exploiting variation in policies across states and time between 1980 and 2016. I find that beer franchise laws significantly reduced craft brewery entry and growth, leading to lower levels of breweries and craft beer production. The effects are largest in states that place restrictions on brewery/wholesaler integration. The findings in this paper indicate that contract termination restrictions, which were legislated to protect wholesalers from upstream brewers, had the effect of encouraging opportunism from wholesalers and inhibited the growth of smaller firms in the industry.
Keywords: L42; L51; 330